The Influence of Real and Accrual Earnings Management on Idiosyncratic Risk With Good Corporate Governance as A Moderating Variable (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the impact of real and accrual earnings management on idiosyncratic risk, with a focus on the moderating role of good corporate governance, proxied by managerial ownership, in manufacturing firms listed on the Indonesia Stock Exchange from 2020 to 2022. Using moderated regression analysis, the findings reveal that both real and accrual earnings management practices negatively affect idiosyncratic risk, suggesting that earnings management may serve as a risk mitigation tool under efficient contracting perspectives. However, managerial ownership exhibits divergent effects: while it strengthens the risk-reducing impact of real earnings management, it unexpectedly amplifies the idiosyncratic risk associated with accrual earnings management, potentially due to managerial motivations to meet financial targets. These results highlight the complex role of corporate governance in earnings management, as it may act as both a stabilizing and risk-amplifying factor depending on the type of earnings management practiced. The study underscores the need for stakeholders to critically evaluate earnings management and corporate governance practices, while encouraging future research to include additional variables to further explain idiosyncratic risk determinants. The study's Adjusted R Square value of 8.1% indicates that other significant factors affecting idiosyncratic risk were not captured in this analysis.